Numerical Modeling of Roof Force in Concrete Liquid Storage Tanks. - pouya soltani; Hassan mirzabozorg (Numerical Methods in Civil Engineering)
Liquid storage tanks are crucial in various applications, such as in industrial processes and water supply systems. It's important to understand how these tanks behave during seismic events to ensure their structural safety. This study examines the force applied to the roof of tanks when the freeboard is insufficient. To conduct the analyses, the Box-Behnken design of the experiment method was used in the study's design. Tanks were modeled using the finite element method combined with smooth particle hydrodynamics. The interaction of the stored fluid with the roof of the tank was assessed using the penalty technique and the soft constraint algorithm. The analysis results showed that the combination of two parameters, the tank length and seismic stimulation, had the most significant impact. However, the fluid height was deemed a non-influential parameter when there was not enough freeboard. Additionally, the results showed that the intensity acceleration spectrum accurately reflects the impact of frequency content on roofed tanks.